2014
DOI: 10.1016/j.jeoa.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Reprint of: Health outcomes and socio-economic status among the mid-aged and elderly in China: Evidence from the CHARLS national baseline data

Abstract: Using a very rich set of health indicators that include both self-reported measures and biomarkers from the CHARLS national baseline data, we document health conditions of the Chinese mid-aged and elderly, examine correlations between these health outcomes and socio-economic status and compare these associations by gender, hukou status and region. As expected, we find that Chinese mid-aged and elderly are facing challenges from chronic diseases including hypertension. Overnutrition has become a bigger problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 39 publications
1
5
1
Order By: Relevance
“…Although little is known about health care equity in Tanzania, our findings are somewhat similar to those of Mtei et al [ 10 ], which indicated a fairly even equal distribution of health care benefits among the members of the community health fund in the country. Our findings differ from those in many African countries, and other countries like China [ 52 ] and India [ 53 ]. For example, studies conducted in Ghana in the population aged 50 and above show a pro-rich inequity whereby those with high incomes accessed more outpatient care than those with low incomes for the same health needs [ 54 , 55 , 56 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Although little is known about health care equity in Tanzania, our findings are somewhat similar to those of Mtei et al [ 10 ], which indicated a fairly even equal distribution of health care benefits among the members of the community health fund in the country. Our findings differ from those in many African countries, and other countries like China [ 52 ] and India [ 53 ]. For example, studies conducted in Ghana in the population aged 50 and above show a pro-rich inequity whereby those with high incomes accessed more outpatient care than those with low incomes for the same health needs [ 54 , 55 , 56 ].…”
Section: Discussioncontrasting
confidence: 99%
“…For example, Marshall and colleagues [ 32 ] reported that hypertension awareness among American and English adults aged 50 years and older was 84% and 76%, respectively, more than 20 percentage points higher than in India. However, the rates in our data resembled those of Chinese adults aged 45 years and older with hypertension, which were 57% for men and 59% for women [ 33 ].…”
Section: Discussionsupporting
confidence: 48%
“…Demographic characteristics included age, gender (male as the reference group), marital status (unmarried or single as the reference group), residency (urban as the reference group), and education (illiterate as the reference group). 37,38 Health habits included body mass index (BMI; kg/m 2 ), smoking (non-smoking as the reference group) and drinking (non-drinking as the reference group). Health comorbidities included self-reported health status (fair or poor as the reference group) and self-reported chronic diseases (no chronic diseases as the reference group).…”
Section: Covariatesmentioning
confidence: 99%